The Framing of Games and the Psychology of Play - Martin Dufwenberg; Simon Gächter; Heike Hennig-Schmidt (University of Bonn, Bonn Graduate School of Economics (BGSE), 2010)
Psychological game theory can provide rational-choice-based framing effects; frames influence beliefs, beliefs influence motivations. We explain this theoretically and explore empirical relevance experimentally. In a 22 design of one-shot public good games we show that frames affect subject's first- and second-order beliefs, and contributions. From a psychological gametheoretic framework we derive two mutually compatible hypotheses about guilt aversion and reciprocity under which contributions are related to second- and first-order beliefs, respectively. Our results are consistent with either.
Keywords: C91; C72; D64; Z13; 330; Framing; psychological game theory; guilt aversion; reciprocity; public good games; voluntary cooperation; Spieltheorie; Öffentliches Gut; Framing; Psychologie; Austauschtheorie (Soziologie); Trittbrettfahrerverhalten; Test